Pengembangan Bahan Ajar Materi Wujud Zat dan Perubahannya Berbasis Budaya Lokal Kelas IV SD: Penelitian - Erlinda Simanjuntak; Hairida Hairida; Rio Pranata; Hery Kresnadi; Bayu Prasodjo (Lembaga Penelitian dan Pengabdian Masyarakat, 2026)
This study aimed to develop local culture-based teaching materials for Natural and Social Science (IPAS) on the topic of States of Matter and Their Changes that were feasible for use in Merdeka Curriculum learning in Grade IV at SD Negeri 10 Sungai Kakap. This research employed a Research and Development (R&D) approach using the ADDIE model, which consisted of five stages: analysis, design, development, implementation, and evaluation; however, the study was limited to the development stage. The research subjects consisted of three expert validators and 30 fourth-grade students at SD Negeri 10 Sungai Kakap. Data were collected through interviews and questionnaires. The validation results indicated that the developed teaching materials demonstrated a very high level of validity, with validation scores of 89.58% for the design aspect, 92.50% for the language aspect, and 88.46% for the content aspect, all of which fell into the very valid category. The practicality test results showed a score of 85.17% in the small-group trial and 88.06% in the large-group trial, both of which were categorized as very practical. Therefore, the local culture-based teaching materials were considered feasible and practical for use in IPAS learning for Grade IV elementary school students.